Sistem Informasi Pengelolaan Mushola Al Amin Puri Teratai Berbasis Web - Agus (CV. Multi Kreasi Media, 2022)
Mushola Al Amin RW 3 Puri Lotus Management System is made and applied web-based, so that it can facilitate the management of Mushola Al Amin, especially treasurers and amil in managing Mushola's finances. In this application uses the PHP programming language, where PHP inserted into HTML is used to build website applications. Currently for the management of its database using MySQL. The application using website media aims to facilitate Dkm in monitoring the financial management of Mushola specifically to mushola financial managers, namely treasurers and amil in receiving, issuing, reporting, and channeling ZISWAF.